Students’ Perspectives on Using E-portfolio for Tertiary-level Academic Writing - Fatema, Kaniz; Nur-A Amanat, Mohammed; Md. Sadman Mobtasin, Munshi (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
This study investigates student perceptions regarding the implementation of electronic portfolios (e-portfolios) in tertiary-level academic writing courses. Utilizing an experimental research design, the study compares the effectiveness and student experiences of e-portfolios against traditional paper-based portfolios within the L2 writing classroom. The research was conducted on two homogeneous groups enrolled in the "English Composition and Communication Skills" course, where variables were kept constant to ensure comparative accuracy. While one group utilized paper-based portfolios, the other group integrated e-portfolios as a core component of their formative assessment. A mixed-methods approach was employed for data collection and analysis. Quantitative data were gathered through a five-point Likert scale questionnaire administered at the end of the semester, while qualitative insights were obtained through focus group discussions (FGDs) using semi-structured frameworks. Quantitative results were processed using Stata statistical software, whereas FGD data underwent a rigorous process of transcription, translation, thematic coding, and categorization. The findings indicate that students using e-portfolios demonstrated superior organizational skills and were better prepared for examinations, despite encountering initial technological hurdles. Ultimately, the research highlights the positive impact of digital tools on student preparation and learning trajectories, offering significant implications for the future of formative assessment in higher education.